Textual and interpersonal metadiscourse markers in political discourse: A case study - Abusalim, Nimer; Zidouni, Siham; Alghazo, Sharif; Rababah, Ghaleb; Rayyan, Mohammad (Cogent arts & humanities, 2022)
This study explores the use of textual and interpersonal metadiscourse markers in political discourse and their role in persuasion. To this end, the study examines four political speeches delivered by Hillary Clinton, an American politician. The speeches were retrieved from YouTube, transcribed and analysed following Dafouz-Milne's (2008) model of metadiscourse markers. In addition, Mai's (2016) taxonomy-which draws on Aristotle's model of persuasion-was used to identify the persuasive functions of metadiscourse markers. The data were analysed qualitatively. The findings show that Hillary Clinton used a variety of metadiscourse markers; in particular, the interpersonal markers were found more frequently used than the textual markers. Within the interpersonal markers, commentaries with the inclusive "we" was the most frequently used, and within the textual markers, the logical markers with the additive "and" were dominant in her speeches. In terms of persuasion, the study found that Clinton used metadiscourse markers to achieve logical appeal (i.e., logos) more often than affective appeals (i.e., pathos). The results are discussed in light of theories of metadiscourse and political discourse.